Globalisation, austerity and social movements: Whose side are we on? (Argumentum, 2013)
In Canada, Australia, Britain and the US the neo-liberal assault is fundamen-tally changing our economies, our wel-fare systems, our cities and the roles, procedures and activities of social workers in the field. In each of the four, ‘fast policy transfer’ (Minton 2009) is resulting in initiatives being ‘shared’ between the four welfare re-gimes – and this means that develop-ments in any one of these societies is relevant and has importance for ana-lysts, theorists and practitioners in each of the others.